Impact of a web‐based psychoeducational intervention on carer mental health quality of life: Results from a pragmatic randomized control trial. (20th December 2022) - O'Rourke, Hannah M; Swindle, Jennifer; Ghosh, Sunita; Chacinski, Dorothy; Baxter, Pamela; Peacock, Shelley; Thompson, Genevieve N; Dubé, Véronique; Holroyd‐Leduc, Jayna; Nekolaichuk, Cheryl; McAiney, Carrie A; Duggleby, Wendy
Abstract: Background: Carers of a person who is living with dementia in long‐term care experience transitions which can challenge their mental health. My Tools for Care‐In Care (MT4C‐In Care) is an online psychoeducational intervention that aims to offer informational, appraisal, and emotional support to assist carers to adapt to the transitions they experience. This presentation will report on the impact of using MT4C‐In Care on carer outcomes including mental health quality of life (primary outcome), and secondary outcomes of social support, hope, self‐efficacy, grief and loneliness. Method: In a single blinded pragmatic randomized control trial, 234 Canadians participated from Alberta, Saskatchewan, Manitoba, and Ontario between February 2020 and October 2021. Carers were eligible if they were ≥18 years of age, had an email address and internet access, and provided physical, emotional or financial care to an adult ≥65 years of age who was living with dementia in a long‐term care home. The intervention group received access to MT4C‐In Care for 2 months; the educational control group received an Alzheimer Society information booklet. Outcomes were assessed using valid and reliable scales at baseline, 2 months and 4 months in telephone interviews. Generalized estimating equations were used to compare changes in the outcomes over time in the treatment and control groups, adjusting for clinically important covariates of gender, age, heart disease, caregiver relationship (spouse vs. non‐spouse) and outcome variables measured at baseline. Result: The primary outcome, mental health quality of life (p = 0.035), improved in both groups over time, along with hope (p = 0.041) and grief (physical distress, p = 0.068). Comparing change in the intervention to the control group, treatment benefit was observed for secondary outcomes of grief (existential concerns; p = 0.095) and social support (total score p = 0.049 and family subscale p = 0.065), but not for the primary outcome of mental health quality of life (p = 0.93). Conclusion: MT4C‐In Care demonstrates benefits for carers in terms of both the primary outcome (mental health quality of life), and secondary outcomes. In comparison to an active educational control group, MT4C‐In Care lessens grief and promotes social support, helping to explain how this intervention promotes carers' mental health.